Designing a prototype of e-solat for pre school childrens based on the spiritual interface design / Nadhirah Ariffin - Ariffin, Nadhirah (2012)
This project is a required subject for the final year students at the Universiti Teknologi Mara. Solat or prayer is one of the pillar in Islam and it the most personal and important practices in our life. Designing the interface can enhance the quality of Muslim children's consistently make to the experience of to know more about Islam. Islam and solat (prayer) are the foundation of the journey in spiritual life. It means to surrender to God (Allah S.W.T) in peace. It has stated in the Quran verses that every Muslims is obligatory to perform solat five times a day. This paper describes a research on designing a prototype of e-solat for pre-school children based on Spiritual Interface Design. The prototype is concentrated on the pre-school children aged between 4 to 6 years old to learn perform solat. The education starts from a childhood. Educating children about solat through technology is also one kind of ways that is commonly used today. Designing this prototype based on the spiritual interface design can help the children to learn performing solat steps by steps with the meaning of every step in solat and the meaning must be related to Allah. Human life is often associated with the spirituality. Spirituality can be defined in many different ways but on this project, the spirituality will be focusing based on the religion on the Islamic perspectives. Static pictures, images, and word could provide positive support for children in their learning process. Despite this, the elements of these interactions design are, at present, still lacking and not emphasis at the kindergarten. Thus, to design on spiritual interface design which could help creating a better way for the learning process for children at "Sikecil Pintar" kindergarten, firstly the user requirements of the user interface that can help children in their learning process will be identified. Secondly, identify the Islamic User Interface element which could help in learning process. At the end of this finding, the design prototype of e-solat for preschools children based on spiritual interface design will be obtained. These finding significantly are the new learning process for solat that are based on the spiritual interface design. Furthermore, children will understand all the meaning in solat although they still cannot read but as long as they know why they do that and memorize all the steps in solat easily.